Governança corporativa em empresas piauienses: estudo de caso de um grupo familiar de capital fechado - Silva Junior, Agnello Rufino da (2018)
Corporate governance has emerged as a way to overcome conflict in the relationship between principal and agent. Its applicability, previously restricted to public companies, has been consolidating in several types of businesses. Private companies and family businesses, are using the principles and practices of corporate governance as a tool to help the professionalization of their management. In this context, the main objective of the present study was to investigate adherence to corporate governance principles and practices in a privately owned Piauí business group. The work is based on the agency theory, the three-dimensional model of development of the family firm of Gersick et al (1997), and the Code of Good Practices of Corporate Governance for private companies of the IBGC. The research is characterized as descriptive, with a qualitative approach and single case study method. The data were collected through the application of check list, interviews, with semi-structured guidelines and available documents. The data were processed with the support of IRAMUTEQ software and the analysis was done through the technique of content analysis. The results show that governance principles such as equity, accountability and corporate responsibility are present in the investigated group, as well as governance mechanisms such as control and conduct bodies. Others like the councils, consultative, administration and fiscal are represented by advisors, centralized mainly in accounting. We also found the future intention to develop mechanisms of corporate governance, with the purpose of strengthening organization.